Is industry size a carrier for wage inequality? A panel study addressing independent variables of inherently different sizes across units - Jarle Aarstad; Olav Andreas Kvitastein (Journal of Risk and Financial Management, 2021)
We address how independent variables of inherently different sizes across units, e.g., small vs. large industries, in panel regression is an advantage interpretively. Analyzing a Norwegian industry panel, we find that wage inequality is a function of industry size, particularly size increase, in an absolute number of firms. A possible reason is that specialized skilled employees negotiate higher wages when there are many legal entities. The findings can also imply that wage inequality is more sensitive to random change, particularly an increase, in large rather than small industries. We conclude that particularly large industries are positive carriers of wage inequality and discuss potential underlying causal mechanisms such as monopolistic competition.
Keywords: 330; fixed effects regression; Gini coefficients; unit size; wage inequality